2013
DOI: 10.1002/pon.3303
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cancer‐related fatigue and personality in patients with breast cancer after chemotherapy

Abstract: There was CRF in patients with breast cancer after chemotherapy. Psychoticism, extroversion/introversion, neuroticism, and lie are correlated with CRF in breast cancer patients after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
(27 reference statements)
1
19
0
3
Order By: Relevance
“…It was also underlined that in addition to conservative therapy of breast cancer, personality, acceptability and neuroticism were important factors responsible for the emergence of depressive symptoms a year after surgical therapy (11). Moreover, in post-chemotherapy patients with breast cancer, cancerrelated fatigue level was found to be correlated with psychoticism, extraversion/introversion, neuroticism and lie subscales of EPI (12). There are few studies on investigation of the relationship between personality traits and the quality of life in the patients with breast cancer.…”
mentioning
confidence: 99%
“…It was also underlined that in addition to conservative therapy of breast cancer, personality, acceptability and neuroticism were important factors responsible for the emergence of depressive symptoms a year after surgical therapy (11). Moreover, in post-chemotherapy patients with breast cancer, cancerrelated fatigue level was found to be correlated with psychoticism, extraversion/introversion, neuroticism and lie subscales of EPI (12). There are few studies on investigation of the relationship between personality traits and the quality of life in the patients with breast cancer.…”
mentioning
confidence: 99%
“…The national statistical services of the SEE registries provided mortality data on a national or regional level, as appropriate. The US mortality data for the total childhood population were provided by the National Center for Health Statistics . Cause of death was coded according to the 10th Revision of the International Statistical Classification of Diseases and Related Health Problems (ICD‐10) .…”
Section: Methodsmentioning
confidence: 99%
“…Although personality has been shown to significantly influence the psychological experience of cancer, Gudbergsson, Fosså, and Dahl have previously pointed out the lack of interest in the scientific field in exploring the effect of personality in the relationship between health and work . For example, Wang et al have shown that psychoticism, extroversion, and neuroticism were correlated with cancer‐related fatigue in breast cancer patients after chemotherapy . Given the deleterious effect of this symptom, it is possible that personality would be associated with cancer survivors' RTW.…”
Section: Commentarymentioning
confidence: 99%
“…6 For example, Wang et al have shown that psychoticism, extroversion, and neuroticism were correlated with cancer-related fatigue in breast cancer patients after chemotherapy. 7 Given the deleterious effect of this symptom, it is possible that personality would be associated with cancer survivors' RTW. Previous studies have also shown that conscientiousness and neuroticism were associated with a longer duration of unemployment and non-RTW for healthy individuals.…”
Section: Commentarymentioning
confidence: 99%